Introduction of household biogas digesters in rural farming households of the Maluti-a-Phofung municipality, South Africa - Nape, K.M.; Magama, P.; Moeletsi, M.E.; Tongwane, M.I.; Nakana, P.M.; Mliswa, V.K.; Motsepe, M.; Madikiza, S. (Journal of Energy in Southern Africa, 2019)
The study aimed to introduce biogas as an alternative source of energy for rural cattle farmers in the Maluti-a-Phofung municipality in the Free State Province, South Africa. To augment the rural farming community’s adoption of the biodigester technology the following initiatives were undertaken: (i) a situational analysis (or diagnostic survey); (ii) training on biogas production in an integrated crop-livestock-bioenergy system; (iii) installation of the biodigesters; and (iv) monitoring and evaluation of the biogas production. Results on the diagnostic survey showed that the main source of energy for cooking was wood in all the farms and availability of water was not a constraint. Prefabricated biodigesters of 6m3 -12m3 were installed in all the households and, after continual feeding of the units with cattle dung, the production of biogas increased gradually. Monitoring of biogas production showed that, in two-thirds of the households, 80% of their cooking needs were met in summer, while in winter biogas production was minimal due to extremely cold weather. Challenges faced included non-adherence to a feeding regime – resulting in a blockage of the biodigester – and lack of feeding. Generally, farmers in the study area showed a high appreciation of the biodigester technology.